ANALISIS SISTEM INFORMASI AKUNTANSI TERHADAP PENERIMAAN KAS TUNAI PASIEN RAWAT JALAN PADA RUMAH SAKIT UMUM DAERAH CIREBON - Dinda Nurfajriyah Putri (EKSYDA: Jurnal Studi Ekonomi Syariah, 2022)
This study aims to determine whether the accounting information system for outpatient cash receipts at the Arjawinangun Regional General Hospital is good. This research is important to provide advice and recommendations to the Arjawinangun Regional General Hospital about the system used. In addition, it also provides recommendations for complete and timely data collection. Recommendations will be considered in improving the hospital accounting information system process in the future. The method used in this study is a qualitative descriptive method, observation, interviews, and documentation. The data used in this study are primary and secondary data. To achieve the research objectives, the researchers made a comparison between theory and practice carried out by the Arjawinangun Regional General Hospital. Based on the results of the study, the accounting information system for outpatient cash receipts at the Arjawinangun Regional General Hospital was quite good, but the information technology and software infrastrukture components were further improved in order to be able to achieve the objectives of the accounting information system at the hospital.